2022-RA-1088-ESGO Chitinase response after 3 cycles of chemotherapy as a promising marker of chemosensitivity an ancillary analysis of the GINECO-ENGOT EWOC-1 trial. (20th October 2022) - Chikh, Karim; Cuerq, Charlotte; Valero, Marie; Colomban, Olivier; Savoye, Aude-Marie; Berton, Dominique; Stefani, Laëtitia; Fabbro, Michel; Blonz, Cyriac; Tredan, Olivier; Noblecourt, Margot; Cojocarasu, Oana; et al.
Abstract : Introduction/Background: Older patients with ovarian cancer have poor outcomes; the geriatric vulnerability score (GVS) was validated as a prognostic factor for survival. During aging the circulating Chitinase 3-like-1 (CHI3L1), and its related chitinase enzymatic activity increase, leading to propose them as 'aging biomarkers'. However, recent data supported the implication of chitinase-like proteins in the proliferation of several cancers. The EWOC-1 trial (NCT02001272 ) showed a lower efficacy of the carboplatin monotherapy (Cmono) arm compared to carboplatin-paclitaxel (CP) in vulnerable patients; a serum sampling was provided on inclusion, after 3 and 6 courses of chemotherapy for the measurement of chitinase activity in each arm (A: standard CP; B: Cmono; C: 3weeks/4 CP), to identify whether its association with patients' outcomes and inversely, the differential impact of the distinct treatment regimens on it. Methodology: Chitinase activity was assessed as previously published. Were analyzed both its absolute value on inclusion ('chitinase baseline') and its kinetics after 3 chemotherapy courses ('chitinase response'). Results: Serum samples could be retrieved for 46/120 patients on inclusion and 33 after 3 chemotherapy courses. Chitinase baseline median activity (in U/L, IQR) was 1727.9 (1459.3; 1878.3) at inclusion, similar in the 3 arms; no association was shown with any of the geriatric vulnerability parameters, nor the GVS, nor overall survival. Chitinase response was significantly different in the 3 arms, with a median (in U/L, IQR) of -160 (-297; 35.2) in the total cohort, -272 (-376; -122) in arm A, 105 (-109; 221) in arm B and -160 (-663; -109) in arm C, p=0.008. High chitinase response was associated with high CA-125 ELIMination rate constant K (KELIM), a marker of chemosensitivity (Fisher exact test, p=0.042). Conclusion: Chitinase activity should not be considered, in the context of ovarian cancer as an aging biomarker, but chitinase response appears as a promising marker of chemosensitivity.